1997
DOI: 10.1128/jvi.71.9.6947-6955.1997
|View full text |Cite
|
Sign up to set email alerts
|

cis elements that contribute to geminivirus transcriptional regulation and the efficiency of DNA replication

Abstract: The A genomic component of the geminivirus tomato golden mosaic virus (TGMV) contains a 5 intergenic sequence that includes the overlapping AL61 promoter and positive-strand origin of DNA replication. The TGMV AL1 protein negatively regulates its own transcription and mediates origin recognition by binding to a repeated motif shared by the AL61 promoter and the viral origin. We examined a series of truncated or mutated 5 intergenic regions in transient expression and replication assays to identify other DNA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(22 citation statements)
references
References 66 publications
(120 reference statements)
2
20
0
Order By: Relevance
“…DNA capable of expressing the AL1 protein with the amino acid alteration in AL4 (AL1 + /AL4 − ) had a small effect on repression of the AL62 promoter (data not shown). Our data is consistent with previous results demonstrating that AL4 has a relatively small effect on autoregulation of AL62 (Gröning et al, 1994;Eagle and Hanley-Bowdoin, 1997).This further demonstrates that AL4 repression plays a limited role in TGMV AL2 and AL3 gene expression.…”
Section: Al4 Contributes To Al2 and Al3 Gene Expressionsupporting
confidence: 93%
“…DNA capable of expressing the AL1 protein with the amino acid alteration in AL4 (AL1 + /AL4 − ) had a small effect on repression of the AL62 promoter (data not shown). Our data is consistent with previous results demonstrating that AL4 has a relatively small effect on autoregulation of AL62 (Gröning et al, 1994;Eagle and Hanley-Bowdoin, 1997).This further demonstrates that AL4 repression plays a limited role in TGMV AL2 and AL3 gene expression.…”
Section: Al4 Contributes To Al2 and Al3 Gene Expressionsupporting
confidence: 93%
“…In the system described in this article, weak expression from the virion sense promoter was attributed to an absence of virus‐derived or virus‐activated cellular factors from the system. Previous experiments performed with WDV and MSV demonstrated that virion sense promoter activity is greater in phloem cells, suggesting that phloem‐specific transcription factors play a role in activating virion sense expression in the infection cycle [21–23]. In addition to this, a cell cycle specificity has been identified for both virion sense and complementary sense promoters of MSV [15].…”
Section: Discussionmentioning
confidence: 92%
“…The ability of Rep to down‐regulate expression of its own promoter has been studied previously. The AL1 protein of tomato golden mosaic virus, for example, has been shown to play a dual role in transcription and replication and it can inhibit its own expression by 20‐fold [4,22]. It is likely that either the modification of Rep, or the interaction of Rep with other viral or cellular proteins, may be involved in regulating the role of Rep as either a participant in viral replication or as a repressor of complementary sense gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A unique characteristic of the members in this clade is the G-Box motif, CACGTG, in their intergenic regions. The G-box is a cis-regulatory element of plant gene promoters and is also involved in the activation of the TGMV Rep gene (Eagle & Hanley-Bowdoin, 1997). In contrast, the DNA-A components of MaMPRV-[PR] and MaMPRV-[PR:Bean] occurring in Puerto Rico are more distantly related, despite being isolated from M. lathyroides and bean, respectively, and cluster with begomoviruses isolated from pepper and R. minima.…”
Section: Discussionmentioning
confidence: 99%